1994
DOI: 10.1002/ajpa.1330930106
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral arthritis and physical activities in the prehistoric Southeastern United States

Abstract: Vertebral arthritis is examined in a prehistoric Native American sample from northwestern Alabama. Both osteophytosis (OP) of the vertebral bodies and osteoarthritis (OA) of the apophyseal facets are highest in the lumbar vertebrae, followed by the cervical and thoracic segments, although differences are much more striking in OP. OA is bilaterally asymmetric, with greater prevalence on the right side in the upper thoracic region. Much of the patterning seen in arthritis in this and other samples is due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
1
33

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 9 publications
13
79
1
33
Order By: Relevance
“…In general, upright bipedal humans exhibit more marked degenerative changes of the spine than other hominoids (Jurmain, 2000). As mentioned above, although human spines tend to be more uniformly affected throughout the vertebral column, previous anthropological investigations revealed that prehistoric and historic human populations vary in terms of the prevalence of degenerative changes of the spine (Bridges, 1994;Moromizato et al, 2007). In addition, there are different patterns between the prevalence of osteophytes on the vertebral body and that of degenerative changes of apophyseal joint (Moromizato et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In general, upright bipedal humans exhibit more marked degenerative changes of the spine than other hominoids (Jurmain, 2000). As mentioned above, although human spines tend to be more uniformly affected throughout the vertebral column, previous anthropological investigations revealed that prehistoric and historic human populations vary in terms of the prevalence of degenerative changes of the spine (Bridges, 1994;Moromizato et al, 2007). In addition, there are different patterns between the prevalence of osteophytes on the vertebral body and that of degenerative changes of apophyseal joint (Moromizato et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Degenerative changes of the lumbar spine were found to be frequent in contemporary and archeological populations, including the Canadian Inuit (Merbs, 1983;Bridges, 1994;Larsen, 1997;Resnick, 2002;and many others). In Japan, the lumbar spine was found to be most affected in the Jomon, Yayoi, early-modern Edo and recent Japanese samples (Wada, 1975;Suzuki, 1978;Fukushima, 1988).…”
Section: Osteophytes On the Vertebral Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the presence of spinal remodeling in the upper thoracic vertebrae is quite stronger in males, than in females. Load-carrying by tumpline, or on the head, have been associated with a peak in OA in the upper thoracic, the middle and lower thoracic, as well as the mid-cervical and lower lumbar vertebrae (Shore 1935;Steward 1979;Kilgore 1984;Jurmain 1990;Bridges 1994;Lovell 1994). However, a peak in OA specifically in the T1 (1 st ) thoracic vertebra has been associated with the method of carrying creels (Merbs 1983;Miles 1989;Sofaer-Derevenski 2000).…”
Section: Dietary Patterns/ Dental Caries and Wearmentioning
confidence: 99%
“…As would be expected given that there are no old adults represented, no severe cases of lumbar osteoarthritis are observed in these remains. Further, because severe osteoarthritis in the cervical vertebrae has been reported in other skeletal series (Bridges, 1994), ad ditionalstudy of the skeletal remains from Ishigaki is warranted.…”
Section: Osteoarthritis (Degenerative Joint Disease)mentioning
confidence: 98%